2021
DOI: 10.1021/acs.est.0c06332
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of Size-Fractionated Airborne Particles from the Sahara Region

Abstract: Diverse airborne microbes affect human health and biodiversity, and the Sahara region of West Africa is a globally important source region for atmospheric dust. We collected sizefractionated (>10, 10−2.5, 2.5−1.0, 1.0−0.5, and <0.5 μm) atmospheric particles in Mali, West Africa and conducted the first cultivation-independent study of airborne microbes in this region using 16S rRNA gene sequencing. Abundant and diverse microbes were detected in all particle size fractions at levels higher than those previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 79 publications
(119 reference statements)
2
19
0
Order By: Relevance
“…Dominant genera recovered in our analyses include those that have previously been linked to African dust, are pathogenic, or both. These include Rubellimicrobium, noted during African dust events in the Eastern Mediterranean and coastal Europe; , Bacillus, an animal and plant pathogen ubiquitous in deserts and Saharan dust; , Escherichia, a human pathogen identified in an African dust intrusion in southern Spain and in Mali; Staphylococcus, a component of the desert soil/dust microbiome and a leading nosocomial antibiotic-resistant pathogen; Sphingomonas, reported in desert dust from North Africa and in the Middle East ,, and common in the aerobacteriome; , Kaistobacter, a soil-inhabiting species but rarely reported in urban and dust-related bioaerosols; Deinococcus and Pontibacter, previously identified in Saharan dust/soil; ,, Streptomyces, a plant pathogen found in desert soil/dust and decaying biomass; and Rothia, an opportunistic soil pathogen.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Dominant genera recovered in our analyses include those that have previously been linked to African dust, are pathogenic, or both. These include Rubellimicrobium, noted during African dust events in the Eastern Mediterranean and coastal Europe; , Bacillus, an animal and plant pathogen ubiquitous in deserts and Saharan dust; , Escherichia, a human pathogen identified in an African dust intrusion in southern Spain and in Mali; Staphylococcus, a component of the desert soil/dust microbiome and a leading nosocomial antibiotic-resistant pathogen; Sphingomonas, reported in desert dust from North Africa and in the Middle East ,, and common in the aerobacteriome; , Kaistobacter, a soil-inhabiting species but rarely reported in urban and dust-related bioaerosols; Deinococcus and Pontibacter, previously identified in Saharan dust/soil; ,, Streptomyces, a plant pathogen found in desert soil/dust and decaying biomass; and Rothia, an opportunistic soil pathogen.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have associated the source of the air-mass with the aerobiome’s community composition (e.g., Bowers et al, 2011 ; Peter et al, 2014 ; Grantham et al, 2015 ; Gat et al, 2017 ; Rahav et al, 2019 ; Tignat-Perrier et al, 2019 ; Lang-Yona et al, 2020 ). Fewer studies have compared the aerobiome’s community composition in terms of particles of different size (e.g., Polymenakou et al, 2008 ; Yamamoto et al, 2012 ; Helin et al, 2017 ; Stern et al, 2021 ). Examining both variables using a single dataset provides a novel opportunity to assess how the microbial community composition of each particle size-class is affected by, or displays, the variance caused by different air-mass sources.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were published between 2004 and 2021 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The affected regions that were studied were Asia (32/51, 62.7%), followed by Europe (9/51, 17.6%), America (6/51, 11.8%), Africa (4/51, 7.8%) and Australia (1/51, 2.0%).…”
Section: Resultsmentioning
confidence: 99%
“…and Coxiela burnetti , as well as Coccidioides spp. fungus and influenza A virus [ 10 , 16 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The remaining studies reported opportunistic pathogens, mostly Bacillus spp., Aspergillus spp., etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation